Anaerobic digestion life cycle assessment (LCA) - Sakhaee, Farhad (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Abstract: Life cycle assessment (LCA) is a tool to evaluate environmental impacts based on products of a process. This research is a case study of wastewater treatment facilities of ERTC (Environmental Resources Training Center), SIUE University, based on available data for two semi-annual sludge quantities (year 2015) from sludge management report. The aim of this study is to compare set of possibilities for a wastewater treatment facility at ERTC. The simulation has been done through SimaPro model. Electricity and methane were considered and the cumulative weight of their impacts has been investigated. Total solids for two semi-annual sludge has been fed to the model in kilogram and different production (electricity and methane) configuration were investigated. The most plausible configuration based on the cumulative environmental impact proposed as best practical solution.